Participation in the multidisciplinary Work Groups - the effects on instituitions - Aleksandra Dolinska; Benjamin Sultan (2023)
Organization and facilitation of workshop to discuss 2022 local Groupe de Travail Pluridisciplinaire (GTP) study on local GTP capacity and impact and co-production literature review findings. Research report presenting results from 2023 GTP surveys at local and national scale. This evidence will help co-develop an impact assessment framework of this climate service co-production model (Make the case for GTP institutionalization)